role of interactions between phage and bacterial proteins within the infected cell: a diverse and puzzling interactome - Roucourt, Bart; Lavigne, Rob (Environmental microbiology, 2009)
Interactions between bacteriophage proteins and bacterial proteins are important for efficient infection of the host cell. The phage proteins involved in these bacteriophage-host interactions are often produced immediately after infection. A survey of the available set of published bacteriophage-host interactions reveals the targeted host proteins are inhibited, activated or functionally redirected by the phage protein. These interactions protect the bacteriophage from bacterial defence mechanisms or adapt the host-cell metabolism to establish an efficient infection cycle. Regrettably, a large majority of bacteriophage early proteins lack any identified function. Recent research into the antibacterial potential of bacteriophage-host interactions indicates that phage early proteins seem to target a wide variety of processes in the host cell - many of them non-essential. Since a clear understanding of such interactions may become important for regulations involving phage therapy and in biotechnological applications, increased scientific emphasis on the biological elucidation of such proteins is warranted.